Jāmiʿ al-tawārīkh : Tārīkh-i Īrān u Islām. Volume 3 - Hamadānī, Rashīd al-Dīn, (Miras Maktoob, ISBN: 9789004365452., 2019)
Rashīd al-Dīn Hamadānī's (d. 718/1319) Jāmiʿ al-tawārīkh has been described by many as the first world history ever. Composed in Persian for the Mongol Il-khans Ghāzān (r. 1295-1304) and Öljeitü (Uljāytu, r. 1304-16), its aim was to set out the history and condition of the Mongol people, conquerors of the world (part one), followed by a description of the other peoples and nations of the world and their histories (part two). Given its unprecedented scope, Rashīd, vizier to both rulers, mobilized a whole team of specialists, informants, and collaborators to assist him in his task. Making use of written and oral sources, the part on the Mongols is a key source on the emergence and organisation of the Mongol empire, while the second part constitutes the first attempt ever at writing a history of the world. The section published in these three volumes describes the history of Iran and Islam. Section: Iran, 3 vols; volume 3.